2018
DOI: 10.1093/brain/awy264
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy subtypes in prodromal Alzheimer’s disease are associated with cognitive decline

Abstract: Alzheimer’s disease is a heterogeneous disorder. Understanding the biological basis for this heterogeneity is key for developing personalized medicine. We identified atrophy subtypes in Alzheimer’s disease dementia and tested whether these subtypes are already present in prodromal Alzheimer’s disease and could explain interindividual differences in cognitive decline. First we retrospectively identified atrophy subtypes from structural MRI with a data-driven cluster analysis in three datasets of patients with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
126
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(151 citation statements)
references
References 33 publications
18
126
0
Order By: Relevance
“…Indeed, the hypometabolic pattern of the "limbic-predominant" subtype identi ed in the present study shows a striking resemblance with a recently described FDG-PET pattern of pathologically con rmed patients with AD dementia with comorbid TDP-43 pathology and hippocampal sclerosis (42). Other studies suggested that the medial-temporal subtype could be additionally affected by small vessel disease (4,43), which would coincide with the numerically highest WMH volume in the "limbic-predominant" subtype in our study. However, this difference did not reach statistical signi cance in our analysis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Indeed, the hypometabolic pattern of the "limbic-predominant" subtype identi ed in the present study shows a striking resemblance with a recently described FDG-PET pattern of pathologically con rmed patients with AD dementia with comorbid TDP-43 pathology and hippocampal sclerosis (42). Other studies suggested that the medial-temporal subtype could be additionally affected by small vessel disease (4,43), which would coincide with the numerically highest WMH volume in the "limbic-predominant" subtype in our study. However, this difference did not reach statistical signi cance in our analysis.…”
Section: Discussionsupporting
confidence: 86%
“…The "typical" subtype included the largest portion of AD dementia cases and was characterized by a typical posterior temporo-parietal pattern of hypometabolism that is commonly linked to AD (13,36). The "limbicpredominant" subtype had most pronounced hypometabolism in the hippocampus and related medial temporal structures which showed similarities to the MRI-de ned medial temporal-predominant atrophy subtypes (4,30,37,38). However, the "limbic-predominant" subtype in the current study also showed hypometabolism in more widespread limbic areas and the frontal lobe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works studying the differential hippocampal-to-cortical distribution of neurofibrillary tangles or the hippocampal-to-cortical volume ratio in patients with Alzheimer's disease or Alzheimer's clinical syndrome concluded that a hippocampal sparing disease process was linked to poorer cognitive and functional prognoses, especially if cortical atrophy predominate in parietal lobes (Na et al, 2016;Risacher et al, 2017;Ten Kate et al, 2018). Indeed, "hippocampal sparing" damage define atypical variants of Alzheimer's disease, known to have faster evolutions due to impairment in executive functions, language or visuospatial abilities, which strongly impact autonomy (Scheltens et al, 2016).…”
Section: Mri Measures Of Differential Hippocampal-to-cortical Atrophymentioning
confidence: 99%
“…Various structural neuroimaging approaches have been used to identify subtypes of Alzheimer's disease (AD) based on patterns of regional atrophy . These studies identified reproducible AD subtypes, namely “limbic‐predominant”, “hippocampal‐sparing”, “typical” (i.e., a combination of limbic‐predominant and hippocampal‐sparing) AD, and, to a lesser extent, “mild atrophy” AD .…”
Section: Introductionmentioning
confidence: 99%